COUNTERFACTUALS IN HISTORIOGRAPHY - Zenonas Norkus (Problemos, 1998)
The article exposes (in brief) the theories of the counterfactuals in analytical philosophy (metalinguistic, ontological and suppositionist) and discusses the conditions of assertability of counterfactuals in historiography. The conviction of some historians that the counterfactuals are essentially forbidden in the scientific historiography is critised on the ground that counterfactuals are implied by the causal statements and statements of the relative causal importance. The admission is made that the traditional (historist) historiography lacks adequate conceptual infrastructure for the detailed analysis of the objectively possible historical alternatives because its only method for validation of such analysis is inference by analogy. The procedure for validation of counterfactuals in economtric history is discussed citing as an exemple the work of Robert Fogel about the impact of the railroads on the economic growth in USA. The irrelevance of Jon Elster's "basic paradox of counterfactuals" for the working historian is asserted on the ground that as a matter of fact there is no empirical social theory capable to endogenize all initial conditions in explanatory arguments where it is instrumental for deduction of explanandum.